Gender and Nominal Power in Multilateral Bargaining - Nicola Maaser; Fabian Paetzel; Stefan Traub (Games, 2022)
In many bargaining situations, the distribution of seats or voting weights does not accurately reflect bargaining power. Maaser, Paetzel and Traub (Games and Economic Behavior, 2019) conducted an experiment to investigate the effect of such nominal power differences in the classic Baron–Ferejohn model. This paper re-analyzes the data from that experiment, looking at gender differences in bargaining behavior and in the effect of nominal weights. We find that women and men differ in particular with respect to the proposed distribution of payoffs and coalition size. By contrast, nominal weights have only minor gender-specific effects.